On the atomic displacement fields of small interstitial dislocation loops - Zhou, Z; Dudarev, S; Jenkins, M; Sutton, A; Kirk, M (2005)
The atomic displacement fields of dislocation loops of size 1-5 nm formed by self-interstitial atoms in alpha-Fe have been calculated using isotropic elasticity theory and anisotropic elasticity theory, and compared with atomic simulations for loops formed by 43-275 self-interstitial atoms. The atomic displacements predicted by anisotropic elasticity theory were in good agreement with those given by the atomistic simulations at distances greater than 3 nm from the loop plane, but the displacements predicted by isotropic elasticity theory showed significant discrepancies at distances up to 15 nm. (c) 2005 Elsevier B.V. All rights reserved.